Impact Of Digital Information Technology On Indonesia’s Economic Growth - Holik, Abdul (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2026)
The advancement of information technology has boosted standard of living among societies. This research tries to find the impact of manufacture growth in information technology on Indonesia’s economic growth. It is a time series analysis with data from the 1st quarter 1994 until 3th quarter 2016. Data used are GDP (Gross Domestic Products), the exchange rate rupiah over USD, and manufacture in information technology. The method of VECM is used to describe bi-directional relationship among variables, and it also enables us to pose endogenity with the exception to specific variable. Empirical results conclude that manufacture’s growth in the information technology has a significantly positive influence on Indonesia’s economic growth, both in the short-term and the long-term. Meanwhile variable exchange rate only has influence in the short term, not in the long term. This finding suggests that the improvement of information technology can boost economic growth nicely. Indonesia as a developing country, should tackle good regulation and promote innovation in this sector to face strict global competitiveness. Innovation in information technology is a high-cost project, so all requirements must be provided proportionally and put it as the top priority. By improving manufactures in information technology, many jobs can be opened; to recruit new employees. This will decrease the unemployment and poverty rates.